Effects of Qi-Fang-Xi-Bi-Granules on Cartilage Morphology and C/ebpα Promoter Methylation in Rats with Knee Osteoarthritis. (28th January 2018) - Wang, Xinxin; Shen, Peng; Tang, Dezhi; Xu, Hao; Qiu, Hongfu; Wu, Tao; Gao, Xiang
Abstract : Objective . To investigate the effects of Qi-Fang-Xi-Bi-Granules (QFXBGs) on cartilage morphology and methylation of C/ebp α (CCAAT/enhancer binding protein α ) at the promoter region. Methods . Knee osteoarthritis (KOA) modeling was performed in rats in accordance with Hulth's method, and control group received sham operation. Eight weeks after KOA modeling, the rats in the KOA modeling group were further divided into 6 groups. Each group was given the appropriate drug. After 8 weeks, half of the rats were used for Micro-CT scan, HE staining, ABH/OG staining, immunohistochemistry, and TUNNEL staining of the knee joint tissue, and the other half were used to examine C/ebp α promoter methylation. Results . The three dose groups of QFXBGs all showed lower degrees of surface fissures and flaking, thicker cartilage layer, and restored chondrocyte and subchondral bone morphology, compared with the KOA model group. C/ebp α -22 promoter methylation levels in the high- and low-dose groups were significantly higher than that in the KOA modeling group (p < 0.05 ), while C/ebp α -2 promoter methylation level in the medium-dose group was significantly higher than that in the KOA modeling group (p < 0.05 ). Conclusions . QFXBGs may alleviate articular cartilage degeneration through promoting C/ebp α -2 or C/ebp α -22 methylation at specific promoter sites.